Associação entre obesidade e sintomas musculoesqueléticos em trabalhadores – uma análise de dados secundários - Azevedo, Renata Trivelato de (Universidade Federal de São Carlos, 2023)
Background: Musculoskeletal symptoms are common and affect people of all ages and may occur in one (single-site) or in several regions of the body (multisite). Obesity may be associated with these symptoms. Objective: To evaluate the association between obesity and single-site and multisite symptoms in a working population. Methods: This is a cross-sectional study with white- and blue-collar workers from several economic sectors. 1,233 workers were evaluated and 644 composed the sample. Personal and occupational characteristics were assessed using a sociodemographic questionnaire. Musculoskeletal symptoms were identified using the Nordic Musculoskeletal Symptom Questionnaire (NMQ). The Body Mass Index (BMI) was calculated and dichotomized in obese (30 kg/m2) and non-obese (<30 kg/m2). Data was descriptively analyzed and through logistic regression in the SPSS program. Results: There was no association between symptoms and obesity, except for the ankle/foot region in male workers. Conclusion: Obesity was associated with the presence of ankle/feet symptoms in men. This association may indicate mechanical overload in the region during activities performed in the standing posture.
Association between obesity and musculoskeletal symptoms in workers – an analysis of secondary data
Keywords: Dor crônica; Saúde do trabalhador; Ergonomia; Prevenção; OUTROS